Factors That Influence The Change Of Mangrove Forest In South Sulawesi, Indonesia - Arfan, Amal (Universitas Negeri Makassar, 2018)
North Belopa located in Luwu regency, South Sulawesi, Indonesia has a mangrove forest area. This study aims to analyze the factors that causes the reduction of mangrove ecosystem in North Belopa. This mangrove forest has undergone extensive changes. In some areas, there are additional mangrove forests however in other areas, there is a reduction. This change is caused by either the physical or anthropogenic factors. The physical factors consist of climate, rainfall, air temperature, humidity, wind, wave and current. Meanwhile, the anthropogenic factors are the conversion of mangrove forests into ponds and garbage disposal. This anthropogenic factor leads to more reduction and dominant than physical factors. As a result, the area of mangrove forest in North Belopa experienced large transformation.